Ileal lactobezoar in extreme premature infant complicated by intestinal perforation: A case report. (July 2022) - Elkhouli, Mohamed; Aleali, Farid; Alzamrooni, Ayah; Chiu, Priscilla; Gauda, Estelle
Abstract: Introduction and importance: Lactobezor is a rare complication that has been reported more in the stomach, however it may be located anywhere in the intestine. Case report: Reported here, is a case of ileal lactobezoar which was complicated by perforation and was mimicking necrotizing enterocolitis in presentation, ex preterm (26 weeks) male infant who presented at day of life 18th (2 days after BM fortification) with hemodynamic instability and intestinal perforation, which was diagnosed by Abdominal X-ray and Ultrasound necessitating urgent laparotomy. Clinical discussion: Laparotomy revealed an area of ileal perforation and an inspissated mass which was confirmed to be lactobezoar by pathology, ileostomy was performed. The baby had an acute postoperative status of hypovolemic shock which was managed clinically, then was restarted on feeds, and the stoma was reversed 9 weeks later. Conclusion: Lactobezoar, although rare, but numbers increased especially with the rise in numbers of extremely preterm infants worldwide, it most commonly presents later in life but in some cases, such as our case it may happen in 1st 2–3 weeks after birth and may cause significant complications as perforation making its differentiation from common GI problems in neonates as NEC more challenging. Highlights: Lactobezoar is a rare GI complication, which may mimic NEC in presentation. In infancy, it usually presents in the stomach, but in our case, it affected other the ileum. It may be complicated, if not early detected, and may cause intestinal perforation, peritonitis, and septic shock. It presents around 14 days after fortification of EBM, but in our case presented earlier after 2 days.